Core-shell structure orientation enhanced ceramic core and preparation method thereof

The core-shell structure composite powder is prepared through the spray drying process and the magnetic field is used to control its directional stacking arrangement. Combined with the oxidation of the metal shell during the sintering process, the problem of poor mixing uniformity of ceramic powder and metal powder is solved, and the ceramic powder is significantly improved. Flexural strength and creep resistance of the core.

CN119330693AActive Publication Date: 2025-01-21SHANGHAI UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411875600.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

In the prior art, the mixing uniformity of ceramic powder and metal powder is poor, resulting in limited improvement in the performance of ceramic core.

Method used

The core-shell structure composite powder with a core of refractory material and a shell of metal is prepared through a spray drying process. Before the molten mixture is injected into the metal mold, the directional stacking arrangement of the core-shell structure composite powder is controlled by a magnetic field, combined with the later sintering process. The metal shell in the mold is oxidized to form a directional ceramic core.

Benefits of technology

The room temperature and high temperature flexural strength and high temperature creep resistance of the ceramic core are significantly enhanced, and the overall performance of the core is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic powder metallurgy, and discloses a core-shell structure orientation enhanced ceramic core and a preparation method thereof.The preparation method specifically comprises the steps that composite powder with the core being refractory material powder and the shell being a metal phase is prepared, the composite powder is added into a dispersing agent according to the proportion, uniform dispersion of the composite powder is achieved through vacuum stirring, and the core-shell structure orientation enhanced ceramic core is obtained; a ceramic core biscuit is prepared through a hot-pressing injection method, meanwhile, a magnetic field is applied to the position of a mold injection opening to regulate and control directional accumulation and arrangement of composite powder, and after the ceramic core biscuit is buried, a metal shell layer is oxidized in the high-temperature sintering process, and the directionally-arranged ceramic core capable of resisting crack propagation is formed. The problem of poor mixing uniformity of two kinds of powder is solved, meanwhile, the composite powder in the molten-state mixture is regulated and controlled by introducing the magnetic field, directional accumulation and arrangement of the composite powder are achieved, and the comprehensive performance of the ceramic core is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic powder metallurgy, and in particular to a ceramic core with a core-shell structure and an orientation-enhanced core and a preparation method thereof. Background Art

[0002] Ceramic core is one of the core components for manufacturing hollow blades of aircraft engines, and its performance plays a vital role in the manufacturing and performance of hollow blades. With the development of high-efficiency air-cooled blades, the internal structure of the blades is becoming more and more complex, which leads to higher requirements for the structure and performance of ceramic cores used to manufacture hollow blades. At present, the performance of some ceramic cores can no longer meet the requirements brought about by the development of blades, so it is urgent to explore and develop new methods to enhance ceramic cores.

[0003] The method for manufacturing ceramic cores is mainly hot die casting. The ceramic powder is mixed with molten paraffin, injected into a metal mold under a certain temperature and pressure, and the liquid mixture is solidified as the temperature decreases. After the mold is filled, the complex-shaped ceramic core can be obtained after solidification. The ceramic core prepared by this method is widely used in the manufacture of aero-engine blades. However, as mentioned above, the performance of the ceramic core needs to be continuously improved to meet the growing performance requirements of hollow blades. At present, in the hot die casting method, the performance of the ceramic core is mainly regulated from the perspective of component optimization, such as adding second-phase particles such as zirconium silicate, zirconium oxide, yttrium oxide, and magnesium oxide. Studies have shown that these second-phase particles can effectively improve the mechanical properties of the ceramic core. There are also studies on strengthening the comprehensive performance of the ceramic core by adding second-phase fibers such as alumina fibers and zirconium oxide fibers. However, these methods are still limited in improving the performance of the ceramic core, and the introduction of fibers will cause the fibers to easily agglomerate, reduce the solid content of the mixture, and thus affect the overall performance of the ceramic core. At the same time, it is also necessary to ensure that the ceramic core has a low shrinkage rate to ensure the high weight of the prepared hollow blade.

[0004] In addition, studies have shown that by adding metal powders such as Al powder, the shrinkage of the ceramic core can be effectively suppressed through the oxidation process of the later sintering process, while improving the bonding strength between particles, while ensuring the low shrinkage rate of the ceramic core, while improving the porosity and mechanical properties of the ceramic core. However, at present, the ceramic powder and metal powder are still mixed in the molten paraffin by mechanical stirring, and the mixing uniformity is poor, which seriously affects the overall performance improvement of the ceramic core.

[0005] The existing patent CN113319271A discloses an oxide-coated powder with a core-shell structure and a preparation method and application thereof, wherein helium and argon are injected into a plasma generator to generate a helium-argon mixed plasma; the powder is mixed with the helium-argon mixed plasma and then injected into water for self-oxidation to obtain an oxide-coated powder with a core-shell structure. The present invention is conducive to achieving densification, homogenization, high bonding and strong matching of the oxide shell layer.

[0006] The existing patent CN103130508B discloses a method for preparing textured boride-based ultra-high temperature ceramics, which uses IVB group metal elements, amorphous boron powder, silicon powder and transition metals as raw materials to prepare a composite powder containing boride seeds and silicide particles; the obtained composite powder is mixed with boride ceramic powder to prepare a slurry, a ceramic green body is prepared by a casting process or a strong magnetic field orientation process, and the ceramic green body is hot-pressed and sintered, thereby preparing a textured boride-based ultra-high temperature ceramic with anisotropic grain morphology.

[0007] In summary, the above two existing patents are to completely solve the problem of poor mixing uniformity of ceramic powder and metal powder in the prior art and limited improvement of ceramic core performance. Summary of the invention

[0008] Based on the above technical problems, the present invention proposes a core-shell structure orientation-enhanced ceramic core and a preparation method thereof, which solves the problem of poor mixing uniformity of ceramic powder and metal powder in the prior art and limited improvement of the performance of the ceramic core.

[0009] To achieve the above-mentioned purpose, the present invention proposes a core-shell structure oriented reinforced ceramic core and a preparation method thereof. The specific technical scheme is as follows:

[0010] A method for preparing a core-shell structure oriented reinforced ceramic core, the preparation method specifically comprising the following steps:

[0011] S1. Preparation of a core-shell composite powder having a refractory core and a metal shell;

[0012] S2. Using a core-shell structure composite powder to form a ceramic core slurry;

[0013] S3. Preparing a ceramic core blank and applying a magnetic field to regulate the directional stacking arrangement of the core-shell structure composite powder;

[0014] S4. After the ceramic core blank is buried, it is sintered at high temperature to form a ceramic core.

[0015] Furthermore, in step S1, a core-shell structure composite powder having a refractory core and a metal shell is prepared by a spray drying process;

[0016] The air flow temperature in the spray drying process is 80-120° C., and the air flow rate is 1-10 kg / h.

[0017] Furthermore, in step S1, the raw material liquid is added into the spray dryer, and the raw material liquid is sprayed into mist liquid droplets by a high-speed centrifugal atomizer, and is dried by co-current contact with hot air;

[0018] The solid phase content in the raw material liquid is 50-70%, the solid phase includes refractory powder and metal powder, the weight percentage of the refractory powder in the solid phase is 70-90%, and the weight percentage of the metal powder in the solid phase is 10-30%;

[0019] The refractory powder is quartz glass powder, alumina powder, calcium oxide powder or magnesium oxide powder, and the particle size of the refractory powder is 1-60 μm and the purity is not less than 99.95%;

[0020] The metal powder is aluminum powder, zirconium powder or copper powder.

[0021] Furthermore, in step S2, the core-shell structure composite powder is added to the dispersant, and a uniformly mixed ceramic core slurry is obtained by vacuum stirring;

[0022] The dispersant is liquid paraffin, the temperature of the liquid paraffin is 70-95°C, the speed of the vacuum stirring is 50-200 rpm / min, the stirring time is 10-36h, and the vacuum degree is 5×10 -2 -6×10 -2 Pa.

[0023] Furthermore, the weight percentage of the core-shell structure composite powder in the ceramic core slurry is 50-70%.

[0024] Furthermore, in step S3, the ceramic core slurry is placed in a core pressing machine, and the ceramic core blank is pressed by a mold, and a magnetic field is applied at the injection port of the mold to control the directional stacking arrangement of the core-shell structure composite powder;

[0025] The molding pressure of the core pressing machine is 1-10MPa, and the magnetic field strength of the magnetic field is 0.1-2T.

[0026] Furthermore, the magnetic field strength of the magnetic field is 0.8-1.2T.

[0027] Furthermore, in step S4, the ceramic core blank is embedded with powder and then sintered at high temperature to form a ceramic core;

[0028] The heating process of high temperature sintering includes multiple stages, the heating range of each stage is 200-400°C, the heating rate of each stage is 3-10°C / min, and the insulation time after heating in each stage is 3-10h;

[0029] The final sintering temperature in the high temperature sintering is 1000-1600°C.

[0030] Furthermore, the multiple stages include: the first stage is from room temperature to 200°C, the heating rate is 3°C / min, and the temperature is kept at 200°C for 3 hours; the second stage is from 200°C to 400°C, the heating rate is 3°C / min, and the temperature is kept at 400°C for 3 hours; the third stage is from 400°C to 600°C, the heating rate is 3°C / min, and the temperature is kept at 600°C for 8 hours; the fourth stage is from 600°C to 900°C, the heating rate is 5°C / min, and the temperature is kept at 900°C for 8 hours; and finally, the temperature is increased from 900°C to 1200°C, the heating rate is 5°C / min, and the temperature is kept for 10 hours.

[0031] The present invention also provides a ceramic core with a core-shell structure orientation reinforcement, and the ceramic core is prepared using the method for preparing the ceramic core with a core-shell structure orientation reinforcement.

[0032] Based on the above technical solution, the present invention has at least the following beneficial effects:

[0033] 1. The present invention proposes a ceramic core with core-shell structure orientation enhancement and a preparation method thereof, and prepares a core-shell structure composite powder with a core of refractory material powder and a shell of metal through a spray drying process, thereby solving the problem of poor mixing uniformity of the two powders.

[0034] 2. The present invention proposes a ceramic core with a core-shell structure orientation enhancement and a preparation method thereof. Before the molten mixture is injected into a metal mold, a magnetic field is introduced to regulate the core-shell structure composite powder in the molten mixture to achieve directional stacking arrangement of the core-shell structure composite powder. Then, through oxidation of the metal shell layer in the subsequent sintering process, a directional arranged ceramic core that resists crack propagation is formed, thereby improving its comprehensive performance.

[0035] 3. The present invention proposes a core-shell structure oriented enhanced ceramic core and a preparation method thereof. The preparation process is simple, can effectively realize the oriented stacking arrangement of the core-shell structure composite powder, and has an excellent effect on strengthening the core performance.

[0036] 4. The present invention proposes a core-shell structure orientation-reinforced ceramic core and a preparation method thereof, which significantly enhances the room temperature and high temperature bending strength and high temperature creep resistance of the ceramic core, and can be applied to the development and application of ceramic cores of other systems. DETAILED DESCRIPTION

[0037] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments of the present invention can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0038] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0039] In order to solve the problem of poor mixing uniformity of ceramic powder and metal powder and limited improvement of ceramic core performance in the prior art, the present invention proposes a ceramic core with magnetically controlled core-shell structure orientation enhancement and a preparation method thereof.

[0040] To achieve the above-mentioned purpose, the present invention provides a ceramic core with a magnetically controlled core-shell structure orientation enhancement and a preparation method thereof. The preparation method of the ceramic core with a magnetically controlled core-shell structure orientation enhancement specifically comprises the following steps:

[0041] S1. Preparation of a core-shell composite powder having a refractory core and a metal shell;

[0042] Specifically, a core-shell structure composite powder with a refractory core and a metal shell is prepared by a spray drying process. The drying air flow temperature in the spray drying process is 80-120°C, and the air flow rate is 1-10 kg / h; the solid phase composition content in the raw material liquid is 50-70%, the weight percentage of refractory powder in the solid phase is 70-90%, and the weight percentage of metal powder in the solid phase is 10-30%.

[0043] The refractory powder is one of quartz glass powder, alumina powder, calcium oxide powder or magnesium oxide powder, the particle size of the refractory powder is 1-60 μm, and the purity is ≥99.95%; the metal powder is one of aluminum powder, zirconium powder or copper powder.

[0044] S2. Add the core-shell structure composite powder to the liquid paraffin and disperse it evenly according to the proportion;

[0045] Specifically, the core-shell structure composite powder is weighed according to a proportion, dried and then added to liquid paraffin, and the composite powder is evenly dispersed in the paraffin by vacuum stirring to obtain a uniformly mixed ceramic core slurry. The weight percentage of the core-shell structure composite powder in the ceramic core slurry is 50-70%, the vacuum stirring speed is 50-200 rpm / min, the stirring time is 10-36h, the temperature of the paraffin is 70-95°C, and the vacuum degree is 5×10 -2 -6×10 -2 Pa.

[0046] S3. Preparing a ceramic core blank and applying a magnetic field to regulate the directional stacking arrangement of the core-shell structure composite powder;

[0047] Specifically, a ceramic core blank is prepared by hot pressing injection, the ceramic core slurry is placed in a core pressing machine, and the ceramic core blank is pressed by a mold, and a magnetic field is applied at the injection port of the mold to control the directional stacking arrangement of the core-shell structure composite powder. The hot pressing molding pressure is 1-10MPa, and the applied magnetic field strength is 0.1-2T.

[0048] S4. After the ceramic core blank is buried, it is sintered at high temperature to form a ceramic core.

[0049] Specifically, after the ceramic core blank is buried with alumina powder as a filler, the metal shell is oxidized during the high-temperature sintering process to form a directional ceramic core that resists crack propagation. The final sintering temperature in the high-temperature sintering is 1000-1600°C, and the heating process of the high-temperature sintering includes multiple stages, the heating range of each stage is 200-400°C, the heating rate of each stage is 3-10°C / min, and the insulation time after each stage of heating is 3-10h.

[0050] The preparation method of the above-mentioned core-shell structure orientation-enhanced ceramic core is further described below in combination with specific implementation data.

[0051] Example 1

[0052] S1. A core-shell structure composite powder with zirconium oxide as the core and zirconium as the shell is prepared by a spray drying process, wherein the drying air flow temperature is 100°C and the air flow rate is 5 kg / h; the solid phase composition content in the raw material liquid is 50%, the weight percentage of zirconium oxide powder in the solid phase is 90%, and the weight percentage of zirconium powder in the solid phase is 10%;

[0053] S2. Weigh 50% of the core-shell structure composite powder according to the weight percentage, dry the composite powder for 12 hours at a drying temperature of 120°C, and then place it in a mixer with melted paraffin wax to achieve full mixing through vacuum stirring. The mixing temperature is 90°C and the vacuum degree is 5×10 -2 Pa, the stirring time is 8h, and a uniformly mixed ceramic core slurry is obtained;

[0054] S3, placing the ceramic core slurry into a core pressing machine, and using a mold to press the ceramic core blank at a pressing pressure of 5 MPa. During the pressing process, a 0.1 T magnetic field is applied at the injection port to obtain a ceramic core blank with a core-shell structure in a directional arrangement;

[0055] S4. Fill the core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 3℃ / min, and it is kept at 200℃ for 3h; the second stage is from 200℃ to 500℃, the heating rate is 3℃ / min, and it is kept at 500℃ for 3h; the third stage is from 500℃ to 800℃, the heating rate is 3℃ / min, and it is kept at 800℃ for 5h; the fourth stage is from 800℃ to 1200℃, the heating rate is 5℃ / min, and it is kept at 1200℃ for 5h; finally, the temperature is increased from 1200℃ to 1600℃, the heating rate is 5℃ / min, and it is kept at 8h, to finally obtain a directionally arranged ceramic core that resists crack propagation.

[0056] The flexural strength of the ceramic core in this embodiment is 52 MPa at room temperature, 58 MPa at 1550° C., and 1.18 mm in deflection at 1550° C.

[0057] Example 2

[0058] S1. A core-shell structure composite powder with alumina as the core and copper as the shell is prepared by a spray drying process, wherein the drying air flow temperature is 100°C and the air flow rate is 5 kg / h; the solid phase composition content in the raw material liquid is 65%, the weight percentage of alumina powder in the solid phase is 88%, and the weight percentage of copper powder in the solid phase is 12%;

[0059] S2. Weigh 65% of the core-shell structure composite powder according to the weight percentage, dry the composite powder for 12 hours at a drying temperature of 120°C, and then place it in a mixer with melted paraffin wax to achieve full mixing through vacuum stirring. The mixing temperature is 90°C and the vacuum degree is 5×10 -2 Pa, the stirring time is 8h, and a uniformly mixed ceramic core slurry is obtained;

[0060] S3, placing the ceramic core slurry into a core pressing machine, and using a mold to press the ceramic core blank, the pressing pressure is 5MPa, and a 1T magnetic field is applied at the injection port during the pressing process to obtain a ceramic core blank with a core-shell structure directional arrangement;

[0061] S4. Fill the core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 3℃ / min, and it is kept at 200℃ for 3h; the second stage is from 200℃ to 400℃, the heating rate is 3℃ / min, and it is kept at 400℃ for 3h; the third stage is from 400℃ to 700℃, the heating rate is 3℃ / min, and it is kept at 700℃ for 5h; the fourth stage is from 700℃ to 1100℃, the heating rate is 5℃ / min, and it is kept at 1100℃ for 6h; finally, the temperature is increased from 1100℃ to 1500℃, the heating rate is 8℃ / min, and it is kept at 8h, finally, a directionally arranged ceramic core that resists crack propagation is obtained.

[0062] The flexural strength of the ceramic core in this embodiment is 59 MPa at room temperature, 73 MPa at 1550° C., and 1.08 mm in deflection at 1550° C.

[0063] Example 3

[0064] S1. A core-shell structure composite powder with magnesium oxide as the core and aluminum as the shell is prepared by a spray drying process, the drying air flow temperature is 100°C, and the air flow rate is 5 kg / h; the solid phase composition content in the raw material liquid is 70%, the weight percentage of magnesium oxide powder in the solid phase is 70%, and the weight percentage of aluminum powder in the solid phase is 30%;

[0065] S2. Weigh 55% of the core-shell structure composite powder according to the weight percentage, dry the composite powder for 12 hours at a drying temperature of 120°C, and then place it in a mixer with melted paraffin wax to achieve full mixing through vacuum stirring. The mixing temperature is 90°C and the vacuum degree is 5×10 -2 Pa, stirring time is 8h, and a uniformly mixed ceramic slurry is obtained;

[0066] S3, placing the taken out ceramic core slurry into a core pressing machine, using a mold to press the ceramic core blank, the pressing pressure is 7MPa, and a 2T magnetic field is applied at the injection port during the pressing process to obtain a ceramic core blank with a core-shell structure directional arrangement;

[0067] S4. Fill the core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200°C at a heating rate of 3°C / min, and it is kept at 200°C for 3 hours; the second stage is from 200°C to 400°C at a heating rate of 3°C / min, and it is kept at 400°C for 3 hours; the third stage is from 400°C to 650°C at a heating rate of 3°C / min, and it is kept at 650°C for 5 hours; the fourth stage is from 650°C to 1000°C at a heating rate of 5°C / min, and it is kept at 1000°C for 6 hours; finally, the temperature is increased from 1000°C to a maximum of 1400°C at a heating rate of 5°C / min, and it is kept at 8 hours to finally obtain a directionally arranged ceramic core that resists crack propagation.

[0068] The flexural strength of the ceramic core in this embodiment is 53 MPa at room temperature, 55 MPa at 1550° C., and 1.08 mm in deflection at 1550° C.

[0069] Example 4

[0070] S1. A core-shell composite powder with a quartz glass core and an aluminum shell is prepared by a spray drying process, wherein the solid phase content in the raw material liquid is 50%, the weight percentage of the quartz glass powder in the solid phase is 80%, and the weight percentage of the aluminum powder in the solid phase is 20%; the drying air flow temperature is 100°C, and the air flow rate is 5 kg / h;

[0071] S2. Weigh 60% of the core-shell structure composite powder according to the weight percentage, dry the composite powder for 12 hours at a drying temperature of 120°C, and then add it to a mixer where the paraffin has been melted. After vacuum stirring, the composite powder and the paraffin are fully mixed. The paraffin temperature is 90°C, the vacuum stirring speed is 100 rpm / min, the stirring time is 8 hours, and the vacuum degree is 5×10 -2 Pa, and a uniformly mixed ceramic slurry is obtained;

[0072] S3, placing the ceramic core slurry into a core pressing machine, and using a mold to press the ceramic core blank, the pressing pressure is 5MPa, and a 0.8T magnetic field is applied at the injection port of the mold during the pressing process to obtain a ceramic core blank with a core-shell structure in a directional arrangement;

[0073] S4. Fill the ceramic core blank with alumina filler and then sinter it at high temperature. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 3℃ / min, and it is kept at 200℃ for 3h; the second stage is from 200℃ to 400℃, the heating rate is 3℃ / min, and it is kept at 400℃ for 3h; the third stage is from 400℃ to 600℃, the heating rate is 3℃ / min, and it is kept at 600℃ for 8h; the fourth stage is from 600℃ to 900℃, the heating rate is 5℃ / min, and it is kept at 900℃ for 8h; finally, the temperature is increased from 900℃ to 1200℃, the heating rate is 5℃ / min, and it is kept at 10h, finally, a directionally arranged ceramic core that resists crack propagation is obtained.

[0074] The flexural strength of the ceramic core in this embodiment is 56 MPa at room temperature, 69 MPa at 1550° C., and 0.87 mm in deflection at 1550° C.

[0075] Example 5

[0076] S1. A core-shell composite powder with a quartz glass core and a zirconium shell is prepared by a spray drying process, the drying air flow temperature is 100°C, and the air flow rate is 5kg / h; the solid phase content in the raw material liquid is 60%, the weight percentage of the quartz glass powder in the solid phase is 85%, and the weight percentage of the zirconium powder in the solid phase is 15%;

[0077] S2. Weigh 70% of the core-shell structure composite powder according to the weight percentage, dry the composite powder for 12 hours at a drying temperature of 120°C, and then place it in a mixer with melted paraffin wax to achieve full mixing through vacuum stirring. The mixing temperature is 90°C and the vacuum degree is 5×10 -2 Pa, the stirring time is 8h, and a uniformly mixed ceramic core slurry is obtained;

[0078] S3, placing the ceramic core slurry into a core pressing machine, and using a mold to press the ceramic core blank, the pressing pressure is 8MPa, and a 1.2T magnetic field is applied at the injection port during the pressing process to obtain a ceramic core blank with a core-shell structure in a directional arrangement;

[0079] S4. Fill the core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200°C, the heating rate is 3°C / min, and it is kept at 200°C for 3 hours; the second stage is from 200°C to 500°C, the heating rate is 3°C / min, and it is kept at 500°C for 3 hours; the third stage is from 500°C to 800°C, the heating rate is 3°C / min, and it is kept at 800°C for 5 hours; the fourth stage is from 800°C to 1200°C, the heating rate is 5°C / min, and it is kept at 1200°C for 5 hours; finally, the temperature is increased from 1200°C to a maximum of 1600°C, the heating rate is 5°C / min, and it is kept at 6 hours to finally obtain a directionally arranged ceramic core that resists crack propagation.

[0080] The flexural strength of the ceramic core in this embodiment is 55 MPa at room temperature, 72 MPa at 1550° C., and 0.65 mm in deflection at 1550° C.

[0081] Comparative Example 1

[0082] S1. A core-shell structure composite powder with a quartz glass core and an aluminum shell is prepared by a spray drying process, the drying air flow temperature is 100°C, and the air flow rate is 5kg / h; the solid phase composition content in the raw material liquid is 50%, the weight percentage of the quartz glass powder in the solid phase is 80%, and the weight percentage of the aluminum powder in the solid phase is 20%;

[0083] S2. Weigh the core-shell structure composite powder according to 60% by weight, dry the composite powder for 12 hours at a drying temperature of 120°C, and then place it in a mixer with melted paraffin wax to achieve full mixing through vacuum stirring. The mixing temperature is 90°C and the vacuum degree is 5×10 -2 Pa, stirring time is 8h, and a uniformly mixed ceramic slurry is obtained;

[0084] S3, placing the taken out slurry into a core pressing machine, and using a mold to press the core blank at a pressing pressure of 5MPa;

[0085] S4. Fill the core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 3℃ / min, and it is kept at 200℃ for 3h; the second stage is from 200℃ to 400℃, the heating rate is 3℃ / min, and it is kept at 400℃ for 3h; the third stage is from 400℃ to 600℃, the heating rate is 3℃ / min, and it is kept at 600℃ for 8h; the fourth stage is from 600℃ to 900℃, the heating rate is 5℃ / min, and it is kept at 900℃ for 8h; finally, the temperature is increased from 900℃ to 1200℃, the heating rate is 5℃ / min, and it is kept at 10h to finally obtain the ceramic core.

[0086] The ceramic core in Comparative Example 1 has a flexural strength of 20 MPa at room temperature, a flexural strength of 36 MPa at 1550° C., and a deflection of 1.87 mm at 1550° C.

[0087] Comparative Example 2

[0088] S1. A core-shell structure composite powder with alumina as the core and aluminum as the shell is prepared by a spray drying process, the drying air flow temperature is 100°C, and the air flow rate is 5 kg / h; the solid phase content in the raw material liquid is 50%, the weight percentage of alumina powder in the solid phase is 80%, and the weight percentage of aluminum powder in the solid phase is 20%;

[0089] S2. Weigh the core-shell structure composite powder according to 60% by weight, dry the composite powder for 12 hours at a drying temperature of 120°C, and then place it in a mixer with melted paraffin wax to achieve full mixing through vacuum stirring. The mixing temperature is 90°C and the vacuum degree is 5×10 -2 Pa, the stirring time was 8 h, and a uniformly mixed ceramic slurry was obtained;

[0090] S3, placing the ceramic core slurry into a core pressing machine, and using a mold to press the ceramic core blank at a pressing pressure of 5 MPa;

[0091] S4. Use alumina filler to fill the ceramic core blank and then sinter it. According to the first stage, the temperature is from room temperature to 200 ℃, the heating rate is 3 ℃ / min, and it is kept at 200 ℃ for 3 hours; the second stage is from 200 ℃ to 400 ℃, the heating rate is 3 ℃ / min, and it is kept at 400 ℃ for 3 hours; the third stage is from 400 ℃ to 600 ℃, the heating rate is 3 ℃ / min, and it is kept at 600 ℃ for 8 hours; the fourth stage is from 600 ℃ to 900 ℃, the heating rate is 5 ℃ / min, and it is kept at 900 ℃ for 8 hours; finally, the temperature is increased from 900 ℃ to a maximum of 1600 ℃, the heating rate is 5 ℃ / min, and it is kept at 10 hours to finally obtain the ceramic core.

[0092] The ceramic core of Comparative Example 2 has a flexural strength of 35 MPa at room temperature, a flexural strength of 42 MPa at 1550° C., and a deflection of 1.52 mm at 1550° C.

[0093] Compared with the results of comparative examples 1-2, the room temperature and high temperature bending strength and high temperature creep resistance of the ceramic core prepared according to the method of the present invention are greater than the results in the comparative implementation, and the performance is significantly improved.

[0094] In some other embodiments, a core-shell structure composite powder with zirconium oxide as the core and zirconium as the shell is prepared, the solid phase content in the raw material liquid is 60% or 70%, the weight percentage of zirconium oxide powder in the solid phase is 70% or 80%, and the weight percentage of zirconium powder in the solid phase is 30% or 20% correspondingly;

[0095] In some other embodiments, a core-shell structure composite powder with a core of aluminum oxide and a shell of copper is prepared, the solid phase content in the raw material liquid is 50% or 70%, the weight percentage of aluminum oxide powder in the solid phase is 70% or 90%, and the weight percentage of copper powder in the solid phase is 30% or 10% correspondingly;

[0096] In some other embodiments, a core-shell structure composite powder with a core of magnesium oxide and a shell of aluminum is prepared, the solid phase content in the raw material liquid is 50% or 70%, the weight percentage of magnesium oxide powder in the solid phase is 70% or 90%, and the weight percentage of aluminum powder in the solid phase is 30% or 10% correspondingly;

[0097] In some other embodiments, a core-shell structure composite powder with a quartz glass core and an aluminum shell is prepared, the solid phase content in the raw material liquid is 60% or 70%, the weight percentage of the quartz glass powder in the solid phase is 70% or 90%, and the weight percentage of the aluminum powder in the solid phase is 30% or 10% accordingly;

[0098] In some other embodiments, a core-shell structure composite powder with a quartz glass core and a zirconium shell is prepared, the solid phase content in the raw material liquid is 50% or 70%, the weight percentage of the quartz glass powder in the solid phase is 70% or 90%, and the weight percentage of the zirconium powder in the solid phase is 30% or 10% correspondingly;

[0099] The use of the above composite powders can also achieve the technical effect that the room temperature and high temperature bending strength and high temperature creep resistance of the ceramic core are better than those of the comparative example.

[0100] In some other embodiments, a core-shell structure composite powder with a core of quartz glass and a shell of copper, a core-shell structure composite powder with a core of alumina and a shell of aluminum, a core-shell structure composite powder with a core of alumina and a shell of zirconium, a core-shell structure composite powder with a core of magnesium oxide and a shell of copper, a core-shell structure composite powder with a core of magnesium oxide and a shell of zirconium, a core-shell structure composite powder with a core of calcium oxide and a shell of copper, and a core-shell structure composite powder with a core of calcium oxide and an aluminum shell are prepared, and the above-mentioned solid phase composition content in the raw material liquid is 50-70%, the weight percentage of ceramic powder in the solid phase is 70-90%, and the weight percentage of metal powder in the solid phase is 10-30%.

[0101] The use of the above composite powders can also achieve the technical effect that the room temperature and high temperature bending strength and high temperature creep resistance of the ceramic core are better than those of the comparative example.

[0102] The directional arrangement of the composite powder after the core-shell joint of ceramic powder as the core and metal phase as the shell is realized by the magnetic field provided by the present invention significantly enhances the room temperature and high temperature bending strength and high temperature creep resistance of the ceramic core, and improves the comprehensive performance of the core. At the same time, the present invention can be applied to the development and application of ceramic cores of other systems.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0104] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0105] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

Claims

1. A method for preparing a core-shell structure oriented reinforced ceramic core, characterized in that: The preparation method specifically comprises the following steps: S1. Preparation of a core-shell composite powder having a refractory core and a metal shell; S2. Using a core-shell structure composite powder to form a ceramic core slurry; S3. Preparing a ceramic core blank and applying a magnetic field to regulate the directional stacking arrangement of the core-shell structure composite powder; S4. After the ceramic core blank is buried, it is sintered at high temperature to form a ceramic core.

2. The method for preparing a core-shell structure oriented reinforced ceramic core according to claim 1, characterized in that: In step S1, a core-shell structure composite powder with a refractory core and a metal shell is prepared by a spray drying process; The air flow temperature in the spray drying process is 80-120° C., and the air flow rate is 1-10 kg / h.

3. The method for preparing the core-shell structure oriented reinforced ceramic core according to claim 2, characterized in that: In step S1, the raw material liquid is added into the spray dryer, and the raw material liquid is sprayed into mist liquid droplets by a high-speed centrifugal atomizer, and is dried by co-current contact with hot air; The solid phase content in the raw material liquid is 50-70%, the solid phase includes refractory powder and metal powder, the weight percentage of the refractory powder in the solid phase is 70-90%, and the weight percentage of the metal powder in the solid phase is 10-30%; The refractory powder is quartz glass powder, alumina powder, calcium oxide powder or magnesium oxide powder, and the particle size of the refractory powder is 1-60 μm and the purity is not less than 99.95%; The metal powder is aluminum powder, zirconium powder or copper powder.

4. The method for preparing a core-shell structure oriented reinforced ceramic core according to claim 1, characterized in that: In step S2, the core-shell structure composite powder is added to the dispersant, and a uniformly mixed ceramic core slurry is obtained by vacuum stirring; The dispersant is liquid paraffin, the temperature of the liquid paraffin is 70-95° C., the rotation speed of the vacuum stirring is 50-200 rpm / min, the stirring time is 10-36h, and the vacuum degree is 5×10-2-6×10-2Pa.

5. The method for preparing a core-shell structure oriented reinforced ceramic core according to claim 4, characterized in that: The weight percentage of the core-shell structure composite powder in the ceramic core slurry is 50-70%.

6. The method for preparing a core-shell structure oriented reinforced ceramic core according to claim 1, characterized in that: In step S3, the ceramic core slurry is placed in a core pressing machine, and the ceramic core blank is pressed using a mold, and a magnetic field is applied at the injection port of the mold to control the directional stacking arrangement of the core-shell structure composite powder; The molding pressure of the core pressing machine is 1-10MPa, and the magnetic field strength of the magnetic field is 0.1-2T.

7. The method for preparing a core-shell structure oriented reinforced ceramic core according to claim 6, characterized in that: The magnetic field strength of the magnetic field is 0.8-1.2T.

8. The method for preparing a core-shell structure oriented reinforced ceramic core according to claim 1, characterized in that: In step S4, the ceramic core blank is embedded with powder and then sintered at high temperature to form a ceramic core; The final sintering temperature in the high-temperature sintering is 1000-1600°C, the heating process of the high-temperature sintering includes multiple stages, the heating range of each stage is 200-400°C, the heating rate of each stage is 3-10°C / min, and the insulation time after heating in each stage is 3-10h.

9. The method for preparing a core-shell structure oriented reinforced ceramic core according to claim 8, characterized in that: The multiple stages include: the first stage is from room temperature to 200°C, the heating rate is 3°C / min, and the temperature is kept at 200°C for 3 hours; the second stage is from 200°C to 400°C, the heating rate is 3°C / min, and the temperature is kept at 400°C for 5 hours; the third stage is from 400°C to 600°C, the heating rate is 5°C / min, and the temperature is kept at 600°C for 8 hours; the fourth stage is from 600°C to 900°C, the heating rate is 8°C / min, and the temperature is kept at 900°C for 8 hours; and finally, the temperature is increased from 900°C to 1200°C, the heating rate is 10°C / min, and the temperature is kept for 10 hours.

10. A core-shell structure oriented reinforced ceramic core, characterized in that: The ceramic core is prepared using the method for preparing a core-shell structure orientation-reinforced ceramic core as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing texturing boride super-high-temperature ceramic

    CN103130508B

  • Oxide coated powder with core-shell structure as well as preparation method and application thereof

    CN113319271A

  • Preparing method of orientation arranged ceramic crystal whisker or fiber reinforced non-corrodible steel based material

    CN101012537A

  • Recovery and efficient use method for ultrafine NdFeB powder

    CN108568522A

  • Core-shell structure ceramic composite powder for thermal spraying and preparation method thereof

    CN112725716A